Menyiapkan Siswa untuk Karir Masa Depan Melalui Pendidikan Berbasis Teknologi : Meninjau Peran Penting Kecerdasan Buatan - Zakaria Zakaria; Tekat Sukomardojo; Sugiyem Sugiyem; Geofakta Razali; Iskandar Iskandar (Journal on Education, 2023)
The future often contains a lot of uncertainty because of the times that change quite rapidly. Current needs may change in a few years. Through the use of technology, students can be better prepared to face future careers. This study aims to look at how the implementation of technology-based education can help students prepare themselves for future careers. This research will be carried out using a descriptive qualitative approach. The data used in this study come from various research results and previous studies that are still relevant to the research discussion. The results of this study then found adequate technological skills to help students in facing highly competitive competition in the world of work later. Then through technology-based education, students can be prepared to face various challenges that are always developing in the future. Therefore, there is a need for various supports to be able to provide students with technology-based education.